Treatment Evaluation in the Prison System of Serbia - Stevanović, Zoran (Zbornik Instituta za kriminološka i sociološka istraživanja, 2010)
The research on the influence of institutional treatments on behaviours and attitudes of convicted persons shows that the effects of the treatments in prison systems in Serbia are very modest. This was shown by the results obtained in testing the correlation between the types of treatments (level of educational work, work engagement, free activities and benefits) and indicators of successful treatments (returns, escapes and disciplinary punishments), where the correlations are relatively low and in most of the cases do not show statistical significance. Only two cases demonstrate a high correlation (0.65) between benefits/return and work engagement/ disciplinary punishment indicators. The results from this study are consistent with the majority of research that has been conducted on institutional treatment of convicted persons. With confidence, we can conclude that there is a ‘crisis’ of the institutional correctional system, and that there is a practice of traditional treatments that are in many ways outdated and do not give an acceptable outcome. This is indicated by the high percentage of recidivism, ranging over 70%. In recent decades, there has been a quest for alternative solutions in the correctional programs that would be able to respond to the demands of the modern penology, and above all to the ‘new profile of offenders’.